Unfavorably Altered Fibrin Clot Phenotype in Women Following Postpartum Hemorrhage of Unknown Cause: Effect of Lower Coagulation Factors - Piróg, Magdalena; Ząbczyk, Michał; Natorska, Joanna; Broniatowska, Elżbieta; Jach, Robert; Undas, Anetta (Thrombosis and Haemostasis, 2024)
Increased clot permeability and susceptibility to lysis have been reported in women with heavy menstrual bleeding. We hypothesized that similar alterations in fibrin clot properties may also be present in women with postpartum hemorrhage (PPH) of unknown cause.To determine fibrin clot properties and their determinants in women after PPH of unknown cause.We studied 52 consecutive women, aged 35 years (27–40), after at least 3 months since PPH of unknown cause and 52 matched controls for age, weight, and fibrinogen. Coagulation factors (F), antithrombin, thrombin generation, along with a comprehensive plasma fibrin clot analysis including fibrin polymerization, clot permeability (Ks), and fibrinolysis efficiency were determined.Women with PPH showed reduced activity of FII (−10.3%), FV (−6.6%), FIX (−6.5%), FX (−7.2%), and FXI (−5.7%) compared with the controls, though all values were within ranges (all p < 0.05). There were no intergroup differences in fibrinogen, FVIII, FXIII, and thrombin generation. The PPH group formed with a delay looser plasma fibrin network (Ks; +16.3%, p = 0.008) with lower maximum absorbance and shorter clot lysis time (CLT; −13.5%, p = 0.001) compared with the controls. On multivariable logistic regression, PPH was independently associated with higher C-reactive protein (per 1 mg/L, odds ratio [OR] = 1.70, 95% confidence interval [CI]: 1.09–2.68), lower FII (per 1%, OR = 0.93, 95% CI: 0.89–0.98), lower FV (per 1%, OR = 0.93, 95% CI: 0.89–0.97), and shorter CLT (per 1 minute, OR = 0.94, 95% CI: 0.90–0.98).Prohemorrhagic fibrin clot properties, with lower, though normal coagulation factors, characterize women with PPH of unknown cause, which suggests novel mechanisms contributing to this type of bleeding.
Keywords: coagulation factors; fibrinolysis; fibrin clot; postpartum hemorrhage